2018
DOI: 10.3390/atmos9030084
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Heavy Rainfall in August 2014 over Japan and Analysis of Its Sensitivity to Sea Surface Temperature

Abstract: This study evaluated the performance of the Weather Research and Forecasting (WRF) model version 3.7 for simulating a series of rainfall events in August 2014 over Japan and investigated the impact of uncertainty in sea surface temperature (SST) on simulated rainfall in the record-high precipitation period. WRF simulations for the heavy rainfall were conducted for six different cases. The heavy rainfall events caused by typhoons and rain fronts were similarly accurately reproduced by three cases: the TQW_5km c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…On the basis of sensitivity experiments on precipitation during August 2014, Minamiguchi et al. (2018) also revealed that warmer SST around Japan could amplify heavy rainfall events associated with typhoons and fronts. In contrast, Iizuka and Nakamura (2019) found no significant relationship between local maximum precipitation and Sea of Japan SST during a heavy rainfall event that occurred over northern Japan in August 2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of sensitivity experiments on precipitation during August 2014, Minamiguchi et al. (2018) also revealed that warmer SST around Japan could amplify heavy rainfall events associated with typhoons and fronts. In contrast, Iizuka and Nakamura (2019) found no significant relationship between local maximum precipitation and Sea of Japan SST during a heavy rainfall event that occurred over northern Japan in August 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Manda et al (2014) performed a sensitivity experiment on a torrential rainfall event that occurred in Japan in mid-July 2012, and they demonstrated that future SST warming in the East China Sea could increase the frequency of extreme precipitation events over western Japan. On the basis of sensitivity experiments on precipitation during August 2014, Minamiguchi et al (2018) also revealed that warmer SST around Japan could amplify heavy rainfall events associated with typhoons and fronts. In contrast, Iizuka and Nakamura (2019) found no significant relationship between local maximum precipitation and Sea of Japan SST during a heavy rainfall event that occurred over northern Japan in August 2013.…”
mentioning
confidence: 99%